Serum acylcarnitine profile in endurance horses with and without metabolic dysfunction. (January 2020) - van der Kolk, J.H.; Thomas, S.; Mach, N.; Ramseyer, A.; Burger, D.; Gerber, V.; Nuoffer, J-M.
Highlights: Mitochondrial fatty acid oxidation following strenuous exercise has not previously been studied in either animals or humans. The availability of carnitine in long-distance endurance horses might limit their performance. These findings might serve as a model for studying fatty acid oxidation under strenuous conditions. Abstract: Mitochondrial β-oxidation is essential in fat metabolism and can be monitored with blood acylcarnitine profiling, as partly degraded fatty acids accumulate as their carnitine esters. To guarantee continuous energy supply during long-distance exercise, endurance horses oxidise considerable amounts of fat in the mitochondrion. In endurance races over 80 km, glycogen depletion is evident in equine slow-twitch high oxidative muscle fibres and as a consequence, horses participating in endurance races over 80 km rely almost entirely on β-oxidation of fatty acids. This study investigated mitochondrial fatty acid β-oxidation in endurance horses exposed to long-distance exercise. Electrospray tandem mass spectrometry analysis of serum acylcarnitine profiles from 10 Arab horses was performed before and after a 160 km endurance race. Results were analysed statistically using ANOVA. Mean speed over the entire race in finishing horses was 16.7 ± 1.2 km/h. Endurance exercise increased mitochondrial β-oxidation approximately eight-fold (pre-race, 5648.62 ± 1508.52 nmol/L; post-race, 44, 243.17 ± 11, 504.45 nmol/L; P = 0.001). In these horses, there was an approximately 17-fold increased lipolysis, as demonstrated by elevated serum concentrations of non-esterified fatty acids (NEFA; pre-race, 0.08 ± 0.08 mmol/L; post-race, 1.32 ± 0.36 mmol/L; P < 0.001). In comparison, four Arab horses with poor performance showed an approximately five-fold increase in mitochondrial β-oxidation (pre-race, 5286.17 ± 3355.16 nmol/L; post-race, 26, 660.57 ± 10, 064.27 nmol/L; P = 0.009); there was a 29-fold increase in NEFA (pre-race, 0.02 ± 0.01 mmol/L; post-race, 0.58 ± 0.07 mmol/L; P = 0.006) in these horses. Similar post-exercise free carnitine:acetylcarnitine ratios in both groups suggest that the availability of carnitine in long-distance endurance horses might limit performance.